Improving the training process of skilled bodybuilders in specially-preparatory phase of the preparatory period - Viktor Dzhym (Kharkiv State Academy of Physical Culture, 2014)
Purpose: to study methods of improving the training process of skilled bodybuilders in a specially-preparatory phase of the preparatory period. Materials and Methods: the study involved 18 skilled bodybuilders are included in the team of the Kharkiv region of bodybuilding. Results: a comparative characteristic of the most commonly used methods of training process in bodybuilding. Developed and justified the optimal technique for skilled bodybuilders, depending on the initial form of the athlete at the beginning of a specially-preparatory phase of training. Shows the dependence of changes in body weight bodybuilder from the training process. Conclusions: on the basis of the research the author proposes an optimal method of training depending on the training microcycle in the run specially-preparatory stage.